The Urgency of Teacher Personality Competence in Modern Education - Rifaudin, Ahmad; Mujib, Abdul; Nugraha, Enung (Electronic Journal of Education, Social Economics and Technology, 2024)
Teacher personality competence in modern education plays a very important role in supporting the quality of learning and holistic student development. This study aims to examine the urgency of teacher personality competence in education today, especially in facing the challenges of an increasingly complex learning environment. The method used in this research is a literature study, with in-depth analysis of various relevant sources regarding the role of teacher personality in education. The results show that personality competence, which includes emotional intelligence, effective communication, and adaptability, is very influential in creating harmonious relationships between teachers and students. Teachers with good personality competence are able to create an environment that supports an effective teaching and learning process and shapes good student character. Therefore, developing teachers' personality competencies needs to be a priority in efforts to improve the quality of education. This research provides important insights into how teachers' personality competencies can enhance students' learning experiences and shape them into individuals who are ready to face future challenges.